Being Arab - Kassir, Samir 1960-2005 (Verso, 2013)
"Before his assassination in 2005, Samir Kassir was one of Lebanon's foremost public intellectuals. In 'Being Arab', a thought-provoking assessment of Arab identity, he calls on the people of the Middle East to reject both Western double standards and Islamism in order to take the future into their own hands. Passionately written and brilliantly argued, this rallying cry for change has now been heard by millions."--p.[4] of cover
Includes bibliographical references
The Arabs are the most wretched people in the world today, even if they do not realize it -- A deep sense of malaise permeates every corner of the Arab world -- The Arab malaise is a period of history and it is now more acute than it was before -- Modernity was not the cause of the Arab malaise -- The Arab malaise is not the result of modernity but of modernity's collapse -- The Arabs' malaise is more a function of their geography than their history -- The worst aspect of the Arabs' malaise is their refusal to emerge from it, but, if happiness is not in sight, some form of equilibrium at least is possible
Keywords: Geschichte 1900-2000; Geschichte; Civilization, Arab; Islam and politics / Arab countries; Arabienbild; Kultur; Araberbild; Arabische Staaten